Egalitarianism: Consciousness-Raising In Women’s Position In The Islamic Family - Wulandari, Wahyuni Retno (SASI, 2022)
Introduction: The Muslim community in the world, including in Indonesia, perceives Islamic family law as very patriarchal. This is because in the discussion related to Islamic family law, it only refers to Al QS. AN-Nisa [4]: 34,which translates women's subordination from men..Purposes of the Research: The purpose of writing this article is to describe a different side of Islamic family law which is always narrated by gender bias by the community, including the Muslim community itself, both in interpretation and even in its implementation carried out in a patriarchal manner. In fact, Al QS. Al-Hujuraat [49]: 13 implies that the rights and obligations of women and men on this earth are purely egalitarian.Methods of the Research: Normative research with the consciousness raising method is in the form of a communication approach related to the position of women in Muslim families, with a communication approach in Muslim communities related to critical awareness to add knowledge of actualization of Muslim communities in Islamic family law which actually does not burden women.Results of the Research: That the excess of men over women must be interpreted as that men are responsible for the maintenance and/or regulation of household affairs, not as rulers, supervisors or superiors of women. So it can be concluded that the concept of a man being the head of the family and a woman being a housewife as conceptualized by Article 31 of the Marriage Law and Article 79 of the KHI is no longer relevant at this time considering that based on the experience of women themselves and data showing an increase in the number of women family heads and women filing for divorce from year to year. As well as the fact that the wife helps her husband to prosper the family and even has to double burden because of it, must also be aware of his independence and not feel isolated because there are economic rights that they must obtain according to the efforts they have done as QS anNisa: 32.